The polyoma virus enhancer cannot substitute for DNase I core hypersensitive sites 2-4 in the human beta-globin LCR. - Tanimoto, K (1999)
The polyoma virus enhancer (PyE) is capable of conferring integration position-independent expression to linked genes in stably transfected erythroid cells after joining to DNase I hypersensitive site (HS) 5 of the human beta-globin locus control region (LCR). In attempting to separate the chromatin opening activity of the LCR from its enhancer activity and to investigate contributions of the individual HS core elements to LCR function, the human beta-globin LCR HS2, HS3 and HS4 core elements were replaced with the PyE within the context of a yeast artificial chromosome (YAC) bearing the whole locus. We show here that, in contrast to its function in cultured cells, the PyE is unable to replace HS core element function in vivo. We found that the PyE substitution mutant LCR is unable to provide either chromatin opening or transcriptional potentiating activity at any erythroid developmental stage in transgenic mice. These data provide direct evidence that the human beta-globin LCR core elements specify unique functions that cannot be replaced by a ubiquitous enhancer activity.